Mechanical Behavior and Failure Analysis of Prosthetic Retaining Screws after Long-Term Use In Vivo. Part 2: Metallurgical and Microhardness Analysis - Youssef S. Al Jabbari, BDS, MS, PhD,1 Raymond Fournelle, PhD,2 Gerald Ziebert, DDS, MS,3 (Journal of Prosthodontics, 2008)
This study involved testing and analyzing multiple retrieved prosthetic retaining screws after long-term use in vivo to: (1) detect manufacturing defects that could affect in-service behavior; (2) characterize the microstructure and alloy composition; and (3) further characterize the wear mechanism of the screw threads.